Building connection against the odds: project workers relationships with people experiencing homelessness. Issue 2 (15th May 2019) - Watson, Clare; Nolte, Lizette; Brown, Rachel
Abstract : Purpose: Trusting and empathic relationships between project workers and people experiencing homelessness (PEH) form the cornerstone for their needs to be met. However, under the UK austerity agenda project workers practice in a context of increasing pressure and limited resources; with relationships often characterised by conditionality and disconnection. The purpose of this paper is to report on a study investigating project workers' experiences of building relationships with PEH living in supported housing projects. Design/methodology/approach: A qualitative design was employed in which focus groups were carried out in six projects, using an opportunity sample of 22 project workers. Data were analysed using thematic analysis, within a social constructionist epistemology. Findings: Three main themes were identified: "Working hard to build connection", "Supporting each other within an unsupportive context" and "Draining but sustaining". Project workers acted out of strong value systems in building relationships with residents against a backdrop of systemic disconnection. Originality/value: Clear clinical implications are put forward with in a Psychologically Informed Environment framework. Services supporting PEH need to be psychologically informed and organisations need to embed reflection within their policies and every day practice. In developing services for PEH interdependence not in/dependence needs to be the aim. Finally, the responsibility for improving the lives of PEH should be placed back on society to provide a context in which PEH can thrive.